Peran Orang Tua Dalam Mengatasi Kecanduan Gadget Pada Anak Usia Dini : Studi Kasus Di RT.002 RW.01, Pondok Pucung, Tangerang Selatan - Dias Amalia Haryanto; Moh. Amin Tohari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Gadgets are one of the electronic items that have become special devices that must be owned by every social creature, because with gadgets, all problems or affairs can be solved more easily and quickly. Addiction is an activity or substance that is done repeatedly and can cause negative effects. This study aims to determine the role of parents in overcoming gadget addiction in early childhood. The theory used in this study is the theory of Kwon, 2013. This study uses a qualitative approach with a descriptive method. Data collection techniques use interviews, observations, and documentation. Analyze data by means of data reduction, data presentation, and summary. The results of this study show the role of parents in overcoming children addicted to gadgets in early childhood.